Penelusuran Epistemologi Kekadiman Alam dalam Tahafut Al-Falasifah dan Tahafut Al-Tahafut - Marzuki, M Fathin Shafly; Wildan, Raina; Rijal, Syamsul (Jurnal Pemikiran Islam, 2023)
This study aims to explore the epistemological debate between Al-Ghazali and Ibn Rushd concerning the concept of the eternity of the world within Islamic philosophy, highlighting the relevance and depth of their thoughts in contemporary Islamic intellectual discourse. Al-Ghazali, through his work "Tahafut Al-Falasifah," critiques the philosophical view that deems the universe as eternal (qadim), emphasizing the importance of revelation and spiritual experience as valid sources of knowledge. Conversely, Ibn Rushd, in "Tahafut Al-Tahafut," defends Aristotle's view on the eternity of the world, illustrating the significance of logic and rationality in understanding the relationship between God, the universe, and humanity. Employing philosophical and historical approaches, this study investigates the methodological differences, arguments, and epistemological conclusions drawn by both thinkers. The findings demonstrate that the dialogue between philosophy and theology in Islam not only enriches the Islamic intellectual tradition but also offers new perspectives in understanding contemporary religious and philosophical issues. This study affirms the significant contributions of Al-Ghazali and Ibn Rushd to advancing Islamic thought, highlighting the importance of an interdisciplinary approach in resolving philosophical and theological dilemmas.AbstrakKajian ini bertujuan untuk mendiskusikan tentang perdebatan epistemologis antara Al-Ghazali dan Ibnu Rusyd mengenai konsep kekekalan alam dalam filsafat Islam, menyoroti relevansi dan kedalaman pemikiran keduanya dalam diskursus intelektual Islam kontemporer. Al-Ghazali, melalui karyanya "Tahafut Al-Falasifah," mengkritik pandangan filsuf yang menyatakan alam sebagai qadim (kekal), menekankan pentingnya wahyu dan pengalaman spiritual sebagai sumber pengetahuan yang valid. Sebaliknya, Ibnu Rusyd dalam "Tahafut Al-Tahafut" membela pandangan Aristoteles tentang kekekalan alam, menunjukkan pentingnya logika dan rasionalitas dalam memahami hubungan antara Tuhan, alam, dan manusia. Melalui pendekatan filosofis dan historis, kajian ini mengeksplorasi perbedaan metodologi, argumentasi, dan kesimpulan epistemologis yang dihasilkan oleh kedua pemikir tersebut. Kajian ini menunjukkan bahwa dialog antara filsafat dan teologi dalam Islam bukan hanya memperkaya tradisi intelektual Islam, tetapi juga memberikan perspektif baru dalam memahami isu-isu keagamaan dan filosofis kontemporer. Kajian ini menegaskan kontribusi signifikan Al-Ghazali dan Ibnu Rusyd dalam memajukan pemikiran Islam, dengan menyoroti pentingnya pendekatan interdisipliner dalam memecahkan dilema-dilema filosofis dan teologis.